2021
DOI: 10.1177/14034948211022434
|View full text |Cite
|
Sign up to set email alerts
|

Risk of SARS-CoV-2 exposure among hospital healthcare workers in relation to patient contact and type of care

Abstract: Aim: We aimed to assess prevalence of IgG antibodies to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and factors associated with seropositivity in a large cohort of healthcare workers (HCWs). Methods: From 11 May until 11 June 2020, 3981 HCWs at a large Swedish emergency care hospital provided serum samples and questionnaire data. Presence of IgG antibodies to SARS-CoV-2 was measured as an indicator of SARS-CoV-2 exposure. Results: The total seroprevalence was 18% and increased during the study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
(27 reference statements)
0
10
1
Order By: Relevance
“…In the previously described Stockholm HCW cohort, all healthcare providers in the capital region of Sweden were asked about participation in a study of past or present SARS-CoV-2 infections [ 8 , 9 ]. Among the major healthcare providers who agreed to participate, a very high proportion (>90%) of the HCWs at work were enrolled, following written informed consent [ 8 , 9 ]. This report focuses on the two largest healthcare providers, Karolinska University Hospital and Stockholm South General Hospital.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the previously described Stockholm HCW cohort, all healthcare providers in the capital region of Sweden were asked about participation in a study of past or present SARS-CoV-2 infections [ 8 , 9 ]. Among the major healthcare providers who agreed to participate, a very high proportion (>90%) of the HCWs at work were enrolled, following written informed consent [ 8 , 9 ]. This report focuses on the two largest healthcare providers, Karolinska University Hospital and Stockholm South General Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…At Karolinska ( Fig 1 ), there were 9449 employees with complete testing data who were also followed for past or future sick leave [ 7 ]. At South Hospital the participants instead completed a questionnaire about symptoms (3981 HCWs) [ 9 ]. All HCWs at work were eligible for inclusion (physicians, nurses, assistant nurses, psychologists, social workers, physiotherapists, care administrators, medical secretaries, occupational therapists, speech therapists and nutritionists etc).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Galanis et al on pooled analysis from worldwide studies observed the seroprevalence of antibodies in HCWs as 8.7% (95% CI 6.7-10.9%), with risk factors of infection recognized to be suboptimal hand hygiene before and after patient contact, longer work hours, and improper personal protective equipment (PPE) usage [10]. Seroprevalence studies in HCWs have indicated the presence of SARS-CoV-2 antibodies ranging from 4% to 22% globally, although there are very few studies that have been conducted in India and none with a prospective design to estimate the incident risk [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%